Design and Simulation of Reset Mechanism of Self-centering Center Rest for Grinding Machine - Yongqiang Zhao; Ruichao Li; Hongling Hou; Changqian Wang; Fei Wang; Haixia Du (Jixie chuandong)
As an auxiliary fixture in the grinding process of slender shaft parts such as lead screw and crankshaft and so on, the self-centering center rest is of great significance to the processing accuracy of slender shaft parts. As an important part of the self-centering center rest, the reset mechanism is related to the positioning accuracy and service life of the self-centering center rest . A rigid reset plate mechanism is studied to realize close contact and timely reset between cam and clamp arm. The parametric design and simulation of reset plate is carried out, and its precise mathematical calculation model is obtained. The contour of the curve groove in the rigid reset plate of a self-centering center rest is solved by using MATLAB software. The correctness of the mathematical model of the reset plate and the feasibility of the design method are verified by using the collaborative virtual simulation functions of MATLAB, UG and Adams software.